2021
DOI: 10.3389/fonc.2021.747586
|View full text |Cite
|
Sign up to set email alerts
|

Editorial: Combating Cancer With Natural Products: What Would Non-Coding RNAs Bring?

Abstract: Editorial on the Research TopicCombating Cancer With Natural Products: What Would Non-Coding RNAs Bring?Natural products are innumerably diverse and exhibit different biological characteristics. Natural products have long been used as medicine for different applications. Chemotherapy is ranked as one of the leading cancer treatments, and a wide range of natural products are currently undergoing clinical evaluation for cancer treatment. However, there is still a large proportion of natural products that are not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 8 publications
2
15
0
Order By: Relevance
“…Non-coding RNAs are a critical component of epigenetics and closely associated with tumour chemotherapy. 11,23,24 In the present study, the expression of lncRNA MEG3, PTTG3P, GAS5, BISPR, MALAT1 and H19 was shown to be altered in SGC7901 cells treated with resveratrol. Of these, H19 was initially recognized as an oncofetal transcript, and aberrant increase in its expression has been observed in malignant tissues in several types of cancers.…”
Section: Discussionsupporting
confidence: 52%
See 4 more Smart Citations
“…Non-coding RNAs are a critical component of epigenetics and closely associated with tumour chemotherapy. 11,23,24 In the present study, the expression of lncRNA MEG3, PTTG3P, GAS5, BISPR, MALAT1 and H19 was shown to be altered in SGC7901 cells treated with resveratrol. Of these, H19 was initially recognized as an oncofetal transcript, and aberrant increase in its expression has been observed in malignant tissues in several types of cancers.…”
Section: Discussionsupporting
confidence: 52%
“…Demonstration of an ability to regulate genetic and epigenetic factors would strengthen the case for using such compounds in cancer therapy. 11,22 Resveratrol has potent anti-inflammatory, anti-oxidative and anti-apoptotic properties; therefore, there have been numerous studies to investigate its antitumour function in recent decades. Non-coding RNAs are a critical component of epigenetics and closely associated with tumour chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations